1997
DOI: 10.2172/600564
|View full text |Cite
|
Sign up to set email alerts
|

Second Generation Advanced Reburning for High Efficiency NO(x) Control.

Abstract: This project is designed to develop a family of novel NO x control technologies, called Second Generation Advanced Reburning which has the potential to achieve 90+% NO x control in coal fired boilers at a significantly lower cost than SCR. The eighth reporting period (July 1-September 30, 1997) included experimental and final report preparation activities. Experiments on high-temperature reactions of sodium carbonate were completed at the University of Texas in Austin. This study revealed that sodium can affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 26 publications
(2 reference statements)
1
22
0
Order By: Relevance
“…Adjustment of the rate coefficient for reaction (2) improved the agreement with experimental data. However, modeling still predicted much lower CO concentrations in flue gas than found in experiments.…”
Section: The Kinetic Model Included 447 Reactions Of 65 C-h-o-n Chemimentioning
confidence: 56%
“…Adjustment of the rate coefficient for reaction (2) improved the agreement with experimental data. However, modeling still predicted much lower CO concentrations in flue gas than found in experiments.…”
Section: The Kinetic Model Included 447 Reactions Of 65 C-h-o-n Chemimentioning
confidence: 56%
“…They found that the optimal N-agent injection point with stoichiometric ratio of 0.99 was needed. Zamansky (1997) and Zamansky and Rusli (1999) found that sodium salt promoters could greatly improve the AR performance. Tree and Clark (2000) studied the detailed species profile of the reaction zone.…”
Section: Advanced Reburning Processmentioning
confidence: 99%
“…Both of these two characteristics can improve or expand the SNCR process temperature window. Overall NO reduction of 85% was obtained in a down-fired furnace by Hampartsoumian and Folayan (2003), 84% by AR-lean and 93% by AR-rich was achieved in a Boiler Simulator Facility (BSF) by Energy and Environmental Research Corporation (EER, USA) (Zamansky, 1997).…”
Section: Advanced Reburning Processmentioning
confidence: 99%
“…The activities during the twelfth reporting period in Phase II (July 1 -September 30, 2000) included testing of AR-Lean in the 3 MW Tower Furnace described elsewhere [1] and modeling the effect of urea co-injection with overfire air on NO x reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Tests conducted in 300 kW and 20 kW pilot-scale facilities [2] demonstrated that efficiency of NO x reduction in Advanced Reburning (AR) could be up to 95% if parameters of AR were optimized. Tests in 3 MW Tower Furnace [3] confirmed that overall NO x reduction in AR can be up to 96%.…”
Section: Introductionmentioning
confidence: 99%